Dynamic PET/CT Imaging of 68Ga-FAPI-04 in Chinese Subjects - Wang, Shuailiang; Zhou, Xin; Xu, Xiaoxia; Ding, Jin; Liu, Teli; Jiang, Jinquan; Li, Nan; Zhu, Hua; Yang, Zhi (Frontiers in Oncology, 2021)
This study aims to further explore dynamic 68Ga-FAPI-04 PET/CT imaging of healthy Chinese subjects and lung cancer patients. Moreover, the variability of 68Ga-FAPI-04 uptake in normal organs was measured to provide a basis for analyzing its biological distribution, interpreting auxiliary images, determining the reliability of image quantification, and monitoring treatment. Six patients (3 subjects without tumors and 3 lung cancer patients) separately underwent 68Ga-FAPI-04 and 2-[18F]FDG PET/CT imaging within 1 week. The biodistribution and internal radiation dosimetry were reported and compared with data previously obtained from Caucasian patients. Moreover, the mean SUV (standardized uptake value) was normalized to body mass or to lean body mass (SUL), and the coefficients of variation (CVs) were calculated and compared for each volume of interest. The average whole-body effective dose was calculated to be 1.27E-02 mSv/MBq, which was comparable with previously reported results of 68Ga-FAPI-04 probes. Furthermore, the SUVmean was slightly higher than the SULmean in most organs; however, the CV of the SULmean for most organs was higher than that of the SUVmean at later time points. In the liver, the CV of the SUVmean was lower (12.7%) than that of the SULmean and was similar to the CV for corresponding 2-[18F]FDG PET/CT value (11.8%). In addition, 68Ga-FAPI-04 PET/CT showed good efficacy for diagnosing lung cancer patients in this study. A comparison of the radiation dosimetry obtained before from a Caucasian population demonstrated no clinically significant differences between these two populations after 68Ga-FAPI-04 injection. The variability in most organs was slightly lower for SUVmean than for SULmean, suggesting that SUVmean may be the preferable parameter for quantifying images obtained with 68Ga-FAPI-04. In addition, 68Ga-FAPI-04 PET/CT imaging is expected to be a promising tool for diagnosing lung cancer.